2015
DOI: 10.1515/biol-2015-0013
|View full text |Cite
|
Sign up to set email alerts
|

Putting the Jigsaw Together - A Brief Insight Into the Tularemia

Abstract: Tularemia is a debilitating febrile and potentially fatal zoonotic disease of humans and other vertebrates caused by the Gram-negative bacterium Francisella tularensis. The natural reservoirs are small rodents, hares, and possibly amoebas in water. The etiological agent, Francisella tularensis, is a non-spore forming, encapsulated, facultative intracellular bacterium, a member of the γ-Proteobacteria class of Gram-negative bacteria. Francisella tularensis is capable of invading and replicating within phagocyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 227 publications
(182 reference statements)
0
5
0
Order By: Relevance
“…The 34 patients with primary hypertension treated in this hospital from June 2012 to June 2014 were selected as observation group. Screening criteria: (1) All the patients met the clinical diagnostic standards developed by “Chinese Hypertension Prevention Guide” (Higgins et al, 2014, Kubelkova and Macela, 2015, Gao et al, 2017a, Gao et al, 2017b, Haitham, 2016); (2) Age between 50 and 75; (3) All patients signed informed consent forms; (4) this study was granted permission and supervised by the Medical Ethics Committee of this hospital. Exclusion criteria: (1) Secondary hypertension patients; (2) Coronary heart disease patients diagnosed by coronary angiography; (3) Diabetes, high cholesterol or cerebral thrombus patients; (4) Patients with liver diseases, kidney diseases and autoimmune diseases/tumor; (5) Patients who had surgery recently or currently have trauma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 34 patients with primary hypertension treated in this hospital from June 2012 to June 2014 were selected as observation group. Screening criteria: (1) All the patients met the clinical diagnostic standards developed by “Chinese Hypertension Prevention Guide” (Higgins et al, 2014, Kubelkova and Macela, 2015, Gao et al, 2017a, Gao et al, 2017b, Haitham, 2016); (2) Age between 50 and 75; (3) All patients signed informed consent forms; (4) this study was granted permission and supervised by the Medical Ethics Committee of this hospital. Exclusion criteria: (1) Secondary hypertension patients; (2) Coronary heart disease patients diagnosed by coronary angiography; (3) Diabetes, high cholesterol or cerebral thrombus patients; (4) Patients with liver diseases, kidney diseases and autoimmune diseases/tumor; (5) Patients who had surgery recently or currently have trauma.…”
Section: Methodsmentioning
confidence: 99%
“…A large number of GWAS reported several hypertension susceptibility gene in primary hypertension patients from Europe, China, Japan and Korea, which laid the foundation for the study of the pathogenesis of hypertension (Hong et al, 2009, Ehret et al, 2008, Maruthamuthu and Kandasamy, 2016, Yang et al, 2016, Zhu et al, 2011). FGF5 is one of the fibroblast growth factors and the existing studies showed that it played an important role in the control of the animal hair growth process (Higgins et al, 2014, Kubelkova and Macela, 2015, Haitham, 2016, Chen et al, 2013). The GWAS found that inside or nearby area of FGF5 gene was the susceptible region of primary hypertension (Dierks et al, 2013, Gao et al, 2017a, Gao et al, 2017b, Lin et al, 2011, Liu et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…There were several huge tularemia outbreaks during World War II in European countries [52], and even today has global distribution, especially in the Middle East [54,55]. The main way of treating this fatal disease is antibiotic therapy, particularly consumption of ciprofloxacin [56,57]. In addition, the mesoporous silica nanoparticles are widely used as a promising compound for the treatment of pneumonia caused by tularemia [58].…”
Section: Tularemiamentioning
confidence: 99%
“…Tularemia is caused by a nonmotile, pleomorphic, Gram-negative coccobacilli bacteria called Francisella tularensis (F. tularensis), and is a common zoonotic infectious disease predominantly seen in the Northern Hemisphere (WHO, 2007;Mead, 2008). The disease is known by various names, such as Francis disease, Ohara disease, Rabbit fever-plague, Horsefly fever, Siberian ulcer and Hunter's disease (Kubelkova, 2015). F. tularensis is a resistant bacterium that can survive in cold and humid environments for weeks; however, it is not resistant to sunlight, high temperature or chlorination (Dikici, 2012).…”
Section: Introductionmentioning
confidence: 99%